Hospital Admission Due to Nephrological Conditions During Hajj: Causes, Healthcare Use, and Short-term Outcomes (Iranian Journal of Kidney Diseases, 2010)
In this retrospective study, records of Iranian Hajj pilgrims who were hospitalized in 2 Iranian hospitals in Mecca and Medina, Saudi Arabia, from 2005 to 2007, were reviewed. Of 600 patients who were hospitalized, 12 (2.0%) were admitted due to nephrological causes, which included kidney calculi (n = 7; 58.4%), acute kidney failure (n = 2; 16.7%), urinary tract infection (n = 1; 8.3%), urinary tract infection and urinary calculus (n = 1; 8.3%), and renal malignancy (n = 1; 8.3%). None of the patients needed referral to other healthcare centers, and all of them were discharged with good condition. Length of hospital stay was 1 to 4 days. There was no association between hospitalization due to nephrological causes and sociodemographic data, healthcare use, and outcome. This inpatient epidemiological study showed 2% of total admissions were related to nephrological conditions in Iranian Hajj pilgrims, most commonly due to easily treated conditions.